Study of ecto and haemo parasites in domestic pigeons (Columba livia domestica) in Sulaimani province, Kurdistan region/Iraq - Abdullah, Shadan Hassan; Mohammed, Aram Ahmad; Saeid, Nahla Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2018)
Pigeons are very well adapted and proliferate without control in urban centers. In this current study, ectoparasites and haemoparasites of 140 adult domestic pigeons (Columba livia domestica) of both sexes were studied, from different localities in Sulaimani province during April to October 2014, since there is no enough data regarding the frequency and identification of ectoparasites and haemoparasites in domestic pigeons in Sulaimani province. All pigeons were examined for the presence of ectoparasites and haemoparasites through checking of blood samples using Giemsa stain. As a result, various species of ectoparasites and haemoparasites were observed. From which, 4 species of lice were detected named Columbicola olumbae (62.5%) followed by Hoborstiella lata (10.42%), Campanulotes compar (4.17%) and Menacanthus stramineus (3.13%). On the other hands, 19.79% of infected pigeons with ectoparasites were diagnosed with the presence of more than 1 lice species. Additionally, examined Giemsa stained smears showed that 55.72% of studied pigeons were harbor haemoparasites including Haemoproteus species (28.20%) followed by Plasmodium species (26.92%) and then Leucocytozoon species (11.53%) consequently
Keywords: Ectoparasite Haemoparasite Pigeon Sulaimani